2017
DOI: 10.3389/fmicb.2017.01042
|View full text |Cite
|
Sign up to set email alerts
|

Co-registered Geochemistry and Metatranscriptomics Reveal Unexpected Distributions of Microbial Activity within a Hydrothermal Vent Field

Abstract: Despite years of research into microbial activity at diffuse flow hydrothermal vents, the extent of microbial niche diversity in these settings is not known. To better understand the relationship between microbial activity and the associated physical and geochemical conditions, we obtained co-registered metatranscriptomic and geochemical data from a variety of different fluid regimes within the ASHES vent field on the Juan de Fuca Ridge. Microbial activity in the majority of the cool and warm fluids sampled wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 75 publications
2
28
0
Order By: Relevance
“…Mesophilic and psychrophilic Gammaproteobacteria, namely SUP05, as well as Epsilonbacteraeota were the dominant organisms present and genes for metabolisms like sulfur oxidation, which can be carried out under aerobic and microaerobic conditions, were most abundant at Anemone (Figs and ). These results are supported by a study of diffuse vent sites within the ASHES vent field, which showed similar community composition and gene expression patterns as those observed at Anemone (Olins et al ., ). The genomic binning results also support this model, as SUP05 populations had higher gene expression levels at Anemone compared to other diffuse vents.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Mesophilic and psychrophilic Gammaproteobacteria, namely SUP05, as well as Epsilonbacteraeota were the dominant organisms present and genes for metabolisms like sulfur oxidation, which can be carried out under aerobic and microaerobic conditions, were most abundant at Anemone (Figs and ). These results are supported by a study of diffuse vent sites within the ASHES vent field, which showed similar community composition and gene expression patterns as those observed at Anemone (Olins et al ., ). The genomic binning results also support this model, as SUP05 populations had higher gene expression levels at Anemone compared to other diffuse vents.…”
Section: Discussionmentioning
confidence: 97%
“…() showed that there were fine‐scale phylogenetic differences in microbial community structure between the two vent fields, with fluid communities at each vent field more closely related to one another than communities found in fluids from the other vent field. In addition, smaller scale spatial studies of multiple diffuse vents within one vent field (Huber et al ., ; Opatkiewicz et al ., ; Perner et al ., ; Akerman et al ., ; Meier et al ., ; Olins et al ., ) show that the microbial community composition is shaped by both the geochemistry as well as the distance between individual diffuse vents. For example, Akerman et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemolithoautotrophic (chemosynthetic) primary production in the deep ocean is most intense in areas around hydrothermal vents, where it is supported by reducing substances formed during hydrothermal circulation through crustal rocks beneath the seafloor (Jannasch and Wirsen, 1979;Karl et al, 1980;Reysenbach and Shock, 2002;Amend et al, 2011;Olins et al, 2017). Global primary production by prokaryotes in subseafloor hydrothermal systems is estimated to be roughly 1.4 Tg C y −1 (McNichol et al, 2018), resulting in hot spots of labile carbon availability around areas of active hydrothermal discharge from the subseafloor.…”
Section: Introductionmentioning
confidence: 99%